The Magnitude of Mortality from Ischemic Heart Disease Attributed to Occupational Factors in Korea - Attributable Fraction Estimation Using Meta-analysis - Jaehyeok Ha; Soo-Geun Kim; Domyung Paek; Jungsun Park (Elsevier, 2011)
Objectives: Ischemic heart disease (IHD) is a major cause of death in Korea and known to result from several occupational factors. This study attempted to estimate the current magnitude of IHD mortality due to occupational factors in Korea. Methods: After selecting occupational risk factors by literature investigation, we calculated attributable fractions (AFs) from relative risks and exposure data for each factor. Relative risks were estimated using meta-analysis based on published research. Exposure data were collected from the 2006 Survey of Korean Working Conditions. Finally, we estimated 2006 occupation-related IHD mortality. Results: For the factors considered, we estimated the following relative risks: noise 1.06, environmental tobacco smoke 1.19 (men) and 1.22 (women), shift work 1.12, and low job control 1.15 (men) and 1.08 (women). Combined AFs of those factors in the IHD were estimated at 9.29% (0.3-18.51%) in men and 5.78% (−7.05-19.15%) in women. Based on these fractions, Korea's 2006 death toll from occupational IHD between the age of 15 and 69 was calculated at 353 in men (total 3,804) and 72 in women (total 1,246). Conclusion: We estimated occupational IHD mortality of Korea with updated data and more relevant evidence. Despite the efforts to obtain reliable estimates, there were many assumptions and limitations that must be overcome. Future research based on more precise design and reliable evidence is required for more accurate estimates.